Antigenic relationships and rapid identification of Peptostreptococcus species. - Wong, M (1980)
Antisera against whole cells of each Peptostreptococcus species (P. anaerobius, P. micros, P. parvulus, and P. productus) were produced in rabbits. When these antisera were reacted against sonically disrupted cells and culture supernatant fluids in Ouchterlony tests, lines of identity were obtained among the antigens from all the species and uninoculated culture medium. When the antisera were subsequently absorbed with the dehydrated culture medium used to grow the peptostreptococci, all cross-reactions in heterologous antigen-antibody combinations were eliminated, leaving only species-specific precipitin arcs. These absorbed antisera, specific for each Peptostreptococcus species by Ouchterlony tests, were used for rapid identification studies. Staphylococcus aureus-bearing protein A was sensitized with each absorbed antiserum. These reagents produced specific coagglutination reactions with suspensions of each Peptostreptococcus reference strain and with 16 clinical isolates. No cross-reactions occurred with the Streptococcus intermedius, Peptococcus magnus, or Peptococcus asaccharolyticus strains tested.